2020
DOI: 10.1016/j.psj.2019.12.046
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature exposure alters the community structure and functional features of the intestinal microbiota in Shaoxing ducks (Anas platyrhynchos)

Abstract: The gut microbiome is a complex ecosystem that contributes to host nutrition and health. However, our current knowledge of the relationship between ambient temperature and gut microbiota of poultry is still limited. The objective of the present study was to characterize the intestinal microbiota of ducks exposed to high ambient temperature. Sixty 60-day-old Shaoxing ducks were allocated to control and heat-treated groups. The ducks in the control group were kept at 25°C, and the ducks in the heat treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
2
12
1
Order By: Relevance
“…A study in layers showed that exposure to high temperature significantly reduced abundance of phylum Firmicutes [ 48 ]. However, these results are contradicted by studies in broilers and in Shaoxing ducks in which exposure to high temperature showed increased abundance of the phylum Firmicutes [ 49 , 50 ]. A study in humans suggest that the effect of stressors on gut microbiota vary across stressors [ 51 ].…”
Section: Discussionmentioning
confidence: 88%
“…A study in layers showed that exposure to high temperature significantly reduced abundance of phylum Firmicutes [ 48 ]. However, these results are contradicted by studies in broilers and in Shaoxing ducks in which exposure to high temperature showed increased abundance of the phylum Firmicutes [ 49 , 50 ]. A study in humans suggest that the effect of stressors on gut microbiota vary across stressors [ 51 ].…”
Section: Discussionmentioning
confidence: 88%
“…For KEGG functional pathway, most microbial genes were mapped to functions related to the metabolism of carbohydrates, amino acids, nucleotide, and energy in the same study [ 18 ]. Tian et al identified transcription, amino acid metabolism, and carbohydrate transport and metabolism as the top three predicted functions of the gut microbial community in ducks under thermoneutral conditions [ 90 ]. Several studies revealed the changes in metabolic functions of gut microbiota of birds under heat stress.…”
Section: Influences Of Heat Stress On Gut Microbiota Structure Composition and Functionalitymentioning
confidence: 99%
“…Zhu et al indicated that high temperatures increased the enrichment of benzoate degradation and cysteine and methionine metabolism pathways but decreased the retinol metabolism and phenylpropanoid biosynthesis pathways in laying hens [ 18 ]. While in ducks, heat stress was found to enrich starch and sucrose metabolism, transcription machinery, energy metabolism, and methane metabolism pathways but lower ABC transporters and several signaling pathways [ 90 ]. Functional changes in the gut microbiota induced by high temperatures provide more information to understand the metabolic role of the gut microbiome in host health.…”
Section: Influences Of Heat Stress On Gut Microbiota Structure Composition and Functionalitymentioning
confidence: 99%
“…Recently, it has been reported that HE affected microbiota diversity in some animals. For example, it caused the increase of Proteobacteria and the decrease of Bacteroides in pig feces ( Xiong et al, 2020 ) and induced significant changes in the variety of duodenum, jejunum, ileum flora in Shaoxing duck ( Tian et al, 2020 ) and cow fecal microbiota ( Chen et al, 2018 ). Neonatal microbial colonization was affected via affecting maternal microbial transmission in late gestational HE in a pig model ( He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%